Pelatihan kewirausahaan inovasi pemasaran dan varian rasa era digital Desa Kedungmaron Kabupaten Madiun - Iskandar, Dicky; Widiasmara, Anny (Nur Science Institute, 2022)
Small and Medium Enterprises (SMEs) of tempeh chips in Madiun Regency are experiencing rapid development, including the